Effect of change in moisture content of Sumatra Forest Honey on total sugar, electrical conductivity and color. Issue 1 (June 2021) - Hidayat, S A; Susilo, A; Masyithoh, D
Abstract: Sumatra forest honey is a type of forest honey produced by Apis dorsata. High humidity in forest environments and the type of open nest can increase the moisture content of honey because of its hygroscopic. The high moisture content has the potential for fermentation cause a decrease in the physicochemical quality of honey and can cause damage to packaging in long-term storage. This research was to know the effect of reducing the moisture content of Sumatran forest honey from 25% to 22% using a vacuum evaporator. The method used an experimental method with a completely randomized design consisting of four treatments and four replications. The results of these parameters are the total sugar content between 72.5% to 76% which has a very significant effect, electrical conductivity between 0.92 and 1.08. ms/cm which gave a significant effect as well as the color intensity of L * a * b * between 14.67 to 17.93 which did not affect the moisture content level of honey. The conclusion of this research showed that decreasing the moisture content of honey using a vacuum evaporator was able to improve the physical and chemical quality of honey.